Highly Variable Femoral Morphology in Osteoarthritic Chinese: Are Prostheses Today Sufficiently Suitable? - Zhang, Yunjie; Wang, Xiaofeng; Wu, Zongming; Xia, Qing; Shao, Yunchao (The Journal of Knee Surgery, 2017)
We aimed to retrospectively investigate the morphology of the resected surfaces of femurs in Chinese patients who underwent total knee arthroplasty (TKA) and to assess the suitability of contemporary femoral components. Measurements on three-dimensional reconstruction after virtual bone cutting were performed on 142 knees from Chinese TKA candidates. The anteroposterior (AP) and mediolateral (ML) dimensions, aspect ratio (ML/AP), and posterior condylar angle (PCA) were measured in the axial plane; the height and length of medial and lateral anterior condyles and the maximal width of the anterior condyles were measured in the frontal plane. Femurs were matched to the prosthesis with the closest AP size. The ML dimensions of femurs were compared with the ML dimensions of the prosthesis. The AP and ML dimensions were significantly larger in male knees (p < 0.01), whereas the difference of aspect ratios was not found to be significantly different between genders (p = 0.26). Both medial and lateral heights of the anterior condyles were significantly higher in men after normalization by AP (p < 0.01 and p < 0.05, respectively). The mean PCA averaged 3.8 degrees for Chinese subjects. The overall prevalence of clinically significant overhang was 6.4% in males and 4.8% in females. The design of femoral prosthesis with alternative ML dimensions of the femoral component is a solution to sufficiently avoid overhang while retaining ideal coverage when dealing with a high variation. Chinese men had higher anterior condyles than women after normalization by AP dimension. The mean PCA was 3.8 degrees for all patients with high variability.
Keywords: total knee arthroplasty; anthropometry; prosthetic design; posterior condylar angle; overhang; anterior condyle